2017
DOI: 10.1016/j.enpol.2017.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the energy efficiency gap - Expected Utility Theory versus Cumulative Prospect Theory

Abstract: Energy efficiency is one of the key factors in mitigating the impact of climate change and preserving non-renewable resources. Although environmental and economic justifications for energy efficiency investments are compelling, there is a gap between the observable and some notion of optimized energy consumption -the so-called energy efficiency gap. Behavioral biases in individual decision making have been resonated by environmental research to explain this gap. To analyze the influence of behavioral biases on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 101 publications
4
42
0
2
Order By: Relevance
“…For LCT, other market failures may lead to low diffusion, whether from foreign or domestic sources, and any diffusion tends to be spatially heterogeneous. For example, firms and households may have imperfect information about potential energy saving investments, and may underinvest in energy efficiency measures, despite the potential for large savings-a phenomenon known as the "energy efficiency paradox" (Allcott and greenstone 2012;häckel, pfosser, and Tränkler 2017;Jaffe and Adam 1994). In addition, when energy efficiency technologies are diffused, their spatial distribution within countries is nonuniform, reflecting heterogeneous socioeconomic, contextual, and local policy conditions (Morton, wilson, and Anable 2018).…”
Section: Will Countries Climb?mentioning
confidence: 99%
“…For LCT, other market failures may lead to low diffusion, whether from foreign or domestic sources, and any diffusion tends to be spatially heterogeneous. For example, firms and households may have imperfect information about potential energy saving investments, and may underinvest in energy efficiency measures, despite the potential for large savings-a phenomenon known as the "energy efficiency paradox" (Allcott and greenstone 2012;häckel, pfosser, and Tränkler 2017;Jaffe and Adam 1994). In addition, when energy efficiency technologies are diffused, their spatial distribution within countries is nonuniform, reflecting heterogeneous socioeconomic, contextual, and local policy conditions (Morton, wilson, and Anable 2018).…”
Section: Will Countries Climb?mentioning
confidence: 99%
“…A small number of the papers identified focussed on the demand side of energy and, in particular, explored barriers to new technology adoption in the construction sector [131,132], small and medium sized enterprises [133], or energy efficiency [134].…”
Section: Testing Barriers Through Implemented Solutionsmentioning
confidence: 99%
“…Research into sustainability, [11]- [17] energy conservation [18]- [21] and environmental preservation [22], [23] are familiar topics for organizations, scholars and researchers. Many studies have indicated the importance of sustainability where greening the organization has become a key strategy for the existence of the business [7], [9], [10], [24], [25].…”
Section: Organization and Sustainabilitymentioning
confidence: 99%